Effects of in-situ residue management on carry over soil moisture conservation practices and growth and productivity of Mustard (Brassica cmpestris) in mid - hill altitude - Kharkrang, Enboklang; Ghosh, P. K. (Umiam : CPGS, CAU, 2009)
The field experiment was conducted at the Water Management field, ICAR Research Complex for NEH Region, Umiam during the year 2008-09 to study the effect of in-situ residue management on carry over soil moisture conservation practices and growth and productivity of mustard (Brassica campestris) in mid-hill altitude. The experiment was laid out in Split Plot design with two main plot treatments, six sub-plot treatments and replicated thrice. The main plot treatments were conventional tillage and zero tillage. The sub-plot treatments consisted of different combinations of mulching materials, comprising maize stalk, Ambrosia weed biomass, FYM and poultry manure, which are tried for their moisture conservation abilities. In general, the soil moisture was higher under zero tillage than conventional tillage. Zero tillage also increased the soil temperature and soil organic carbon (OC). Adoption of FYM @10 t/ha + maize stalk cover (MSC) poultry manure @5t/ha + Ambrosia @5 t/ha + MSC or Ambrosia @10 t/ha +MSC proved to be more efficient than other organic materials, regardless of the tillage. Further, all the mulching treatment improved the soil physical properties and resulted in much better yield than the control. The Bulk densities of surface (0-15 cm) soils during the growing season of both maize and mustard crops were significantly affected by different conservation measures. In general, available Nitrogen (N) and potassium (K) was found to be higher in the conventional tillage plots, but the amount of available phosphorous was higher in the zero tillage system. In terms of yield, the mulching practices (maize stalk with or without Ambrosia) performed better and produced 1.5 to 4.5 times higher yield than the control. The improvement in the crop performance was evident from the difference of the treated plots, when compared with the control, where the lack of moisture caused lower growth, branching and pod formation leading to lower biomass and relative turgidity. Taking the economics of cultivation into consideration, Ambrosia@ 10t/ha was found to be superior to all the other treatments, for both the tillage system.
Keywords: Agronomy; Mustard productivity; Soil moisture; Zero tillage